Effects of myofunctional appliance in children with sleep-disordered breathing: Pengaruh alat myofunctional pada anak dengan gangguan pernapasan saat tidur - Pawinru, Ardiansyah S.; Gunawan, Muh. Chaerul (Makassar Dental Journal, 2025)
Several sleep-related breathing disorders include sleep-disordered breathing (SDB), upper airway resistance syndrome, and obstructive sleep apnoea. Myofunctional therapy involves exercises designed to improve coordination, strength, and control of the orofacial muscles. This review was prepared in accordance with PRISMA and adapted to journal guidelines. This study shows that myofunctional therapy is an effective non-surgical approach to managing sleep-disordered breathing in children. Through orofacial muscle exercises, this therapy has the potential to reduce the severity of SDB symptoms and improve children's sleep quality. Myofunctional therapy not only helps to overcome airway obstruction caused by enlarged adenoids or tonsils, but also contributes to the improvement of overall orofacial function. It is concluded that a holistic approach to SDB management can provide better results than traditional methods such as the use of continuous positive airway pressure or surgical intervention.